Aktualisasi Kemandirian dan Entrepreneur Melalui Program Bazar Santri - Yunita, Ita; Machrus, Ali; Fauzi, M. Asif Nur (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
This research is motivated by the strategic potential of Islamic boarding schools regarding self-reliance, independence, and community participation, in the context of developing the people's economy, then the actualization of independence and entrepreneurial skills of students through the Tsanawiyah 4 Santri Bazaar Program at the Sidogiri Islamic Boarding School. This program is designed to provide practical experience in running a business, as well as developing an entrepreneurial spirit among students. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, participatory observation, and documentation. The results of the study show that this bazaar program has succeeded in developing the independence of students, which is shown through increased initiative, responsibility, and independent decision-making abilities. In addition, students also show increased entrepreneurial skills, including business management, marketing strategies, and financial management. Students learn to work in teams, overcome challenges, and innovate in attracting customers. The Tsanawiyah 4 Santri Bazaar Program not only contributes to the development of practical skills, but also builds the character of students who are creative, independent, and have an entrepreneurial spirit. Thus, this program can be used as a model for other Islamic boarding schools in integrating entrepreneurship education into their curriculum. Recommendations for further development include increasing the intensity of entrepreneurship training, providing adequate resources, and collaborating with the surrounding community to expand the impact of the program.